EXPLORING THE ROLE OF EMOTIONAL INTELLIGENCE ON ACADEMIC PERFORMANCE: A CASE STUDY OF HIGH SCHOOL STUDENTS - Giri, Abhijit; Singh, Sunita; Pandey, Preeti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Emotional Intelligence (EI) has become an important element of education, as an important companion to other traditional intelligence measures such as IQ, to reflect student success. EI is defined as the ability to perceive, assess and manage emotions; use them to help academia, exercise resilience, and positively interact with others. Crains' study had two aims, to expose the relation of EI and academic achievement in high school, and to assess the difference in EI across demographic variables. The researcher employed a mixed-method approach, using descriptive and exploratory methods. The researcher used systematic questionnaires to gather descriptive data from a striated random sample 100 students. The data was analyzed using SPSS statistical applications of correlation regression and ANOVA. The results of the study endorsed a positive correlation between EI & academic success, with a correlation coefficient of 0.65; in other words, students who were higher EI would yield higher academic success. The regression results suggested that EI accounted for 42.3% of the variability in academic successful or academic achievement, providing evidence that EI has predictive validity. The study noted that socio-emotional skill sets: self- awareness, empathy, and emotional regulation are as highly influential in determining academic achievement above and beyond cognitive skills. It was concluded that EI development should be included in the curriculum and teacher practice for academic support.